2017
DOI: 10.20944/preprints201711.0004.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Semi-Pilot Photocatalytic Rotating Reactor (RFR) with Supported TiO<sub>2</sub> /Ag Catalysts for Water Treatment

Abstract: Abstract:A four stage semi-pilot scale RFR reactor with ceramic disks as support for TiO2 modified 9 with silver particles was developed for the removal of organic pollutants. The design presented in 10 this article is an adaptation of the rotating biological reactors (RBR) and its coupling with the 11 modified catalyst provides additional advantages to designs where a catalyst in suspension is used. 12The optimal parameter of rotation was 54 rpm and the submerged surface of the disks offer a total

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…A significant improvement in absorption due to surface plasmon resonance between 500 and 600 nm was achieved as shown, resulting from the interaction of the metal particles with the incident light. The improvement of the photocatalyst efficiency by the inclusion of metallic particles such as silver could be confirmed by Fermi energy levels which were displaced at values close to the bottom of the conduction band; the accumulation of electrons influences the plasmon absorption band, which can improve the photocatalytic activity of a material in the visible region [20,23] our results indicates that the bandwidth of the titanium modified with silver was 2.9 EV.…”
Section: Doping Of the Catalyst And Characterization Of Tio 2 /Agmentioning
confidence: 52%
See 2 more Smart Citations
“…A significant improvement in absorption due to surface plasmon resonance between 500 and 600 nm was achieved as shown, resulting from the interaction of the metal particles with the incident light. The improvement of the photocatalyst efficiency by the inclusion of metallic particles such as silver could be confirmed by Fermi energy levels which were displaced at values close to the bottom of the conduction band; the accumulation of electrons influences the plasmon absorption band, which can improve the photocatalytic activity of a material in the visible region [20,23] our results indicates that the bandwidth of the titanium modified with silver was 2.9 EV.…”
Section: Doping Of the Catalyst And Characterization Of Tio 2 /Agmentioning
confidence: 52%
“…A significant improvement in absorption due to surface plasmon resonance between 500 and 600 nm was achieved as shown, resulting from the interaction of the metal particles with the incident light. The improvement of the photocatalyst efficiency by the inclusion of metallic particles such as silver could be confirmed by Fermi energy levels which were displaced at values close to the bottom of the conduction band; the accumulation of electrons influences the plasmon absorption band, which can improve the photocatalytic activity of a material in the visible region [20,23] our results indicates that the bandwidth of the titanium modified with silver was 2.9 EV. The results of X-ray diffraction (DRX), as well as the results of scanning electron microscopy (SEM) and those of the analysis of the chemical composition of the catalyst (SEM-EDS) have been published in a previous article [24]; they indicated that the actual percentage of deposited silver was 3.4% and that there was no evidence of alteration in the composition of the crystalline phase of the catalyst significantly due to the inclusion of metallic silver.…”
Section: Doping Of the Catalyst And Characterization Of Tio2/agmentioning
confidence: 52%
See 1 more Smart Citation
“…Conventional treatments are inadequate or deficient for the elimination of emerging contaminants; advanced oxidation processes are a viable alternative [7]. Photocatalysis has proven to be efficient in eliminating these pollutants [8,9].…”
Section: Introductionmentioning
confidence: 99%